Pelayanan Pas Kecil Bagi Nelayan di Wilayah Kerja Kantor Unit Penyelenggara Pelabuhan Kelas III Sadai - Rizwanda, Rizwanda; Sari, Jayanti Armida (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2024)
Inspection and small-value passport issuance services are activities carried out to assist fishermen in the issuance of certificates of nationality of vessels. This article is written to understand the improvement of the work area surveying service of UPP Level 3 bureau in Sadai and the issuance of Pas Kecil for fishermen. The research methodology used is qualitative and based on a case study design. Qualitative is used to analyze how well the UPP Sadai office measures and issues the certificate. The data obtained are presented in the form of primary data and secondary data. Primary data was obtained through interviews with informants using targeted sampling techniques, while secondary data was obtained from the document of UPP Sadai office. The results of this work showed that the quality of public services of UPP Sadai Sadai office was good in terms of tangibility, reliability, responsiveness, safety and empathy. However, this institution still faces challenges in increasing the number of fishers managing the documents, such as low public awareness of the importance of the document because there is no need to travel long distances to catch fish.